Distribuição espaço-temporal dos homicídios entre adolescentes por macrorregião de saúde no Estado do Ceará, 2000 a 2015 - Vale, Cecília Regina Sousa do (2018)
Violence has become a major focus of concern, not only in Brazil but throughout the world. This dissertation aims to characterize the magnitude and patterns related to Firearm Homicides among adolescents by the Microregion of Health of the state of Ceará, between the years 2000 to 2015, in order to calculate the coefficients of HAF mortality, to describe the temporal trend, to identify patterns of distribution and spatial agglomeration and areas of risk. Ecological study of time series and spatial analysis having the macro-regions of health (MRS) of the state of Ceará as the unit of analysis. All data on the deaths of adolescents (12 to 18 years old) related to firearm homicide (HAF) in the years 2000 to 2015 (X93-ICD-10) were included. The HAF data come from the National System of Information on Mortality-DATASUS and the population data obtained in the IBGE, in the National Census of Population (2000 and 2010) and population estimates for the intercensary years (2001-2009 and 2011-2015). The general mortality coefficient HAF - CBMAF general (2000-2015), per quadrennium (2000-2003, 2004-2007, 2008-2011, 2012-2015) and adjusted HAF coefficient (CAMAF) was used as the dependent variable. The analyzes were performed using Stata® version 11.2. Data were stratified by sex / gender, race / color, residence MRS. To determine the differences between the groups by MRS, the relative risk was estimated with 95% CI and the chi-square test (χ2) was used, considering statistical significance p<0.05. For the analysis of the time trend, the Poisson Joinpoint regression (version 4.4.2) was used. For each segment, the Annual Percentage Change (APC) and the Mean Annual Percentage Change (AAPC) with 95% CI were estimated and tested. MRS were used for the spatial analysis of HAF and calculation of auto correlation indicators and construction of thematic maps through ArcGIS® version 9.3 and TerraView® version 4.2.2. For the spatial dependence analysis, the G and Gi * indexes (Gistar) of Getis-Ord were used. The maps were used considering the municipalities with statistically significant differences (p <0.05). Kulldorff's retrospective statistics were used to identify high-risk space-time clusters. In the study period, 59 municipalities presented HAF notification (n / N = 59/184, 32.1%), with 11.4% of patients with CBMAF between> 2.0 to 4.0 / 100,000 inhabitants. and 7.6% between> 4.0 to 8.0. There was a significant increase of general CBMAF among adolescents (AAPC = 7.1, p <0.05). There was growth in MRS, except Fortaleza between 2000-2002 (Fortaleza 3.8%, Sobral 4.7%, Central Sertão 5.6%, Litoral Leste / Jaguaribe 6.0% and Cariri 10.0%). There was a significant temporal trend of growth of CBMAF in MRS Cariri (AAPC =10.0, p <0.05), between male individuals (AAPC = 8.6, p <0.05) and selfreported brown = 7.1, p <0.05). There are high CAMAF identified in the central region of the state (Moran's Index = 0.12, p <0.01). The standards recognized by the Getis-Ord Gi for the adjusted data in the total period showed aggregates of high values of CAMAF concentrating in the center-south region of the state, highlighting the municipalities of Milhã, Quixeramobim, Senador Pompeu, Pedra Branca, Mombasa, Piquet Carneiro, Acopiara and Orós, although without statistical significance (z-score = 0.13 and p = 0.90). There is an urgent need to propose and develop public policies for the prevention of lethal violence among adolescents, considering the specific contexts of each of the five MRS in Ceará, as well as conducting new studies.